2016
DOI: 10.1002/mds.26665
|View full text |Cite
|
Sign up to set email alerts
|

Subliminal gait initiation deficits in rapid eye movement sleep behavior disorder: A harbinger of freezing of gait?

Abstract: Background Muscle activity during REM sleep is markedly increased in people with REM sleep behavior disorder (RBD) and people with Parkinson’s disease (PD) who have freezing of gait. This study examined if individuals with RBD, who do not have a diagnosis of PD, show abnormalities in gait initiation that resemble the impairments observed in PD and whether there is a relationship between these deficits and the level of REM sleep without atonia. Methods Gait initiation and polysomnography studies were conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 49 publications
2
39
0
Order By: Relevance
“…5,11,31 Previous studies have also shown deficits in step execution in people with FOG. 11,32 Therefore, impaired APAs are common to PD, with FOG causing additional deficits during step execution (push-off and first step).…”
Section: Discussionmentioning
confidence: 99%
“…5,11,31 Previous studies have also shown deficits in step execution in people with FOG. 11,32 Therefore, impaired APAs are common to PD, with FOG causing additional deficits during step execution (push-off and first step).…”
Section: Discussionmentioning
confidence: 99%
“…However, multivariable analysis in the same study failed to establish its risk factor effect [16]. Although gait disorders have been found in polysomnographyconfirmed RBD patients [46,47] and it was hypothesized that FOG and RBD might share a common physiopathology [48], the relationship between RBD and FOG was not confirmed [16,18,24]. In other two studies, RBDSQ at baseline didn't show significant difference between transitional freezers and non-freezers [18,24], which was supported by a previous finding that there was no freezing difference between the patients with probable RBD and without RBD [49].…”
Section: Sleepmentioning
confidence: 96%
“…21,87 Isolated RSWA has been associated with positive neurodegenerative biomarkers such as loss of smell or color vision 88 and has been associated with gait freezing and cognitive impairment in PD. 89,90 Rapid eye movement sleep without atonia amounts have also been shown to progress over time in patients with idiopathic RBD 91 and have been associated with a higher risk of phenoconversion to PD in idiopathic RBD. 92 Isolated RSWA may also phenoconvert to idiopathic RBD, as shown in a recent study, with 7% to 14% of patients developing clinical RBD during longitudinal follow-up.…”
Section: Diagnosis Of Rbdmentioning
confidence: 99%
“…23,30,31,41,42,45,89,99101 In addition, neuropsychological deficits of dysexecutive, attentional, visuoperceptual, and short-term memory impairments appear to progress over time, 38,44,96,102107 and neurophysiological markers such as electroencephalographic slowing, 108111 and neuroimaging studies have also demonstrated findings indicating likely underlying synucleinopathy pathology.…”
Section: Clinical Implications Of Rbdmentioning
confidence: 99%